The Influence of the Use of Online Learning Media (Whatshap, Google Form and Google Meet) on Online Islamic Religious Education Learning during the Covid-19 Pandemic - Nurhakim Nurhakim; Sunhaji Sunhaji (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Education is one of the most basic things for humans. The progress and development of a nation cannot be separated from the development of education in a nation. To advance education, it’s necessary to have innovation and creativity in learning. In the decade of this century the development of technology has increasingly become necessity for humans and can not be separated from education. To produc an innovative education, there is a need for collaborative learning with technology. Therefore, educators must conquer technology in order to make Indonesian education competitive. When the world experienced the covid 19 outbreak. Indonesia was the affected. Therefore, learning activities are required to innovate, one of which is by using technology as a learning medium, to achieve learning targets in the curriculum during the pancemic, so it is necessary to measure the relevance of online learning media based on Whatshapp, Google Form and Google Meet for learning during the covid 19 Pandemic. How the relevance of the use of the media in learning activities during the covid 19 pandemic.